Knowledge and practice of smoking among secondary School students of Kathmandu district. - Samba, Eena (2012)
SUMMARY: Cigarette smoking is increasing at an alarming rate in developing country, including Nepal which is a risk factor of non communicable disease such as cardiovascular and cancer and also it contribute to greater illness and death from number of other condition. Nowadays globally it emerged as epidemic and cigarette smoking is risk factor for the six of the eight leading causes of premature death in the world. The objective of the study was to assess the knowledge and practice of smoking among secondary school student of Kathmandu district, find out the knowledge regarding health hazard of smoking, secondhand or passive smoking, meaning of smoking and also find out the smoking habit or prevalence of smoking among secondary school. The study was a descriptive, cross-sectional survey among school adolescent of grade 9 and 10 of Kathmandu district. The systematic random sampling applied and study area was select through purposive sampling. Data collection was carried out by using anonymous self-administered questionnaire. The sample size of the study was 104. Informed verbal consent was obtained from the school authority and students. Data was calculated by using SPSS on the basis of study objective. The studies revealed that out of total adolescent students under study, 26(25%) were smoker. Among them 12(46.15%) were regular smoker, 5(19.23%) were occasional smoker and 9(34.61%) were ex-smoker. Majority (62.5%) smokers were from age group 10-14 years, where 55% male smoker and 45% female smoker. Adolescent from Brahmin family were found more likely to smoke as compared to those from Janajati family. Out of total respondents, 28.85% adolescent smoker were from family at least one member smoker similarly 21.15% smoker from family no member smoker. This study found that 16(10.67%) adolescent student were having good knowledge and 83(83.84%) having some knowledge about health hazard of smoking. Among them, more female (62.5%) have good knowledge than male (37.5%). Smoking was higher among those with good knowledge (43.75%) then those with some knowledge (22.89%). It was also found that 25(96.15%) adolescent student want to quit smoking and 9(34.61%) respondents had already quit smoking. The study revealed that the parental smoking habit influence the behavior on their children.